Permisividad sancionadora de la legislación ecuatoriana, para reprimir infracciones por violencia de género como problema de salud pública - Cabrera Zhuma, Fernando Patricio (2016)
The Constitution of the Republic of Ecuador, article 66 provides that the State will guarantee all people a life free of violence, whether in the public or private sector to take steps to try to prevent, eliminate or punish all forms of violence, but that which is exercised in a special way against women, girls, boys and adolescents, which is eradicating violence in all areas. The State will try to formulate and implement policies aimed at achieving equality between men and women, as well as to establish mechanisms to prosecute and punish crimes of domestic violence. In this way, since the constitutional sphere it is preventing and controlling violence domestic, directly related to gender-based violence, where the term by itself, does not distinguish male or female, but considered violence from different types and it is conditioned by different types of violence that are committed to different members of the familywithout specifying the violence exercised only against women. Violence against women in different parts of the world, and by different scholars has been seen as a problem of public health, since it is a problem that must be treated from a comprehensive way, and the same if a victim of an act of 5 violence has a direct relationship with the health sector and the emotional balance of the person. Since theory has tried to give a connotation to differentiate system sex genre, where you can define a condition exists to determine that women are not born but made, giving the term sex a feature which serves to differentiate hormonal or genital, traits that is dealt with from a biological aspect. Different treaties and international conventions try to placate the violence that is exercised, especially against women, but in some articles if it makes reference to equality between men and women, call on gender equity.